Identities in the Literature of South Tyrol after 1965 - Siller, Barbara (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2012)
This dissertation analyzes the topic of identity in the German and Italian literature of South Tyrol. Identity questions are particularly fascinating in this region, since it experienced a territorial change, which had a major impact on the region and its people; Before 1919 South Tyrol was part of Austria, while after 1919 it became part of Italy. The thesis chooses the literary period after 1965 since this date is the beginning of a significant change in the way of narrating identity. If beforehand the protagonists mainly presented more or less fixed types and roles within the political game of identity and were thus mostly polarized within the plot of the story, after 1965 the protagonists gradually move away from a rather collective identity construction and start to create their identities individually. This thesis uses various theoretical approaches to shed light on identities, such as Ricoeur’s reflection on the Self and the Other, Foucault’s analysis of discourse strategies, Levinas’ understanding of human encounter, Sen’s writing on politicized identities, Freud and Kristeva’s interpretation of the uncanny. Through a close-reading of the literary texts two main themes have been identified: firstly, memories and spaces in connection to identities. Therefore, the first literary chapter shows the centrality of remembering for the construction of identities and the way in which collective and individual memories are intertwined. In the texts memories are told as fragmentary constructions always depending on the story-teller’s perspective. As spaces, which inform identities, mountains and villages play an essential role in the narratives. Their portraits follow the tradition of Anti-Heimat-literature, a literary tendency within the German speaking literature of the Seventies and Eighties. Tourism also has an impact on the identity-construction of the protagonists and on the perception of space. A special form of space is the family unit within society, which is mainly shown as being a patriarchal one. The narratives outline the decisive role of the father and brother within the family, especially in regard to the lives of the mother and daughter as well as in regard to political decisions. The political elite in the region propagated for long time the separation of the ethnic groups. Subsequently, in the texts the ethnic aspect comes into play: inter-ethnic marriages between Italians and Germans are shown as prohibited and if this rule is not respected, punishment will follow. The woman’s body assumes political importance and the woman feels obliged to follow stricter norms than the man. Furthermore, religion is crucial for the construction of identities in the analyzed narratives. The church services the political structures by making the people submissive and filling them with fear and shame. The second theme identified in the texts is identity in connection to narrativity. Based on Ricoeur’s belief that narrativity paves the way to tell oneself in many different ways, this chapter outlines the possibilities which narrativity opens up, but also its limits. On one hand, language and narration allows for a very creative space, for the protagonists as well as for the authors. Many protagonists escape any one singular narration and try out different paths. Several authors make use of multi voiced and polylingual narrative strategies as well as different point of views within the narration. Numerous identity stories loose their chronological feature to be replaced by an associative, multi perspective, fragmentary narrative. However, beside the narrativity a very essential role is given to stories that are not told through words: the texts illustrate many forms of silence and this thesis will classify some of their functions. Here again, the politics of identity is vital. Various identity constructions and deconstructions are demonstrated in the literature. Dichotomic structures are always placed within the Italian and German context, hybrid structures show a way out from the polarization, transitory identities and patchwork identities move the identity towards being a fragile, multilayered, continuous individual process which every human being carries out. The dissertation argues that after 1965 the literary texts from the region of South Tyrol undergo essential changes in their way of narrating protagonists and themes. Although the ethnic polarization is still a topic problematized in various texts, the topic of identity moves away from a narrow, collective construction of one’s Self. The individual links up to the postmodern and global processes and is keen to make his/her own choices. The formal structures of the text reveal a similar tendency: poststructuralist narrative strategies enter the literature of the region gradually. To conclude, the thesis illustrates that the literature from South Tyrol during the period 1965 to date undergoes fundamental and irreversible changes in regard to the representation of the theme of identity.
Identitäten im Literaturraum Südtirol seit 1965
Keywords: German, Ph.D.; Ph.D. Trinity College Dublin, 2012